2010
DOI: 10.3892/ijmm_00000527
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-seryl-aspartyl-lysyl-proline attenuates renal inflammation and tubulointerstitial fibrosis in rats

Abstract: Abstract. It has been reported that N-acetyl-seryl-aspartyllysyl-proline (Ac-SDKP) attenuates renal and cardiac inflammation as well as fibrosis in hypertensive rats. In this study, we investigated these effects using a unilateral ureteral obstruction (UUO) model. Eighteen male Wistar rats were randomly divided into three groups: control, UUO/vehicle and UUO/Ac-SDKP groups. Animal models of renal inflammation and tubulointerstitial fibrosis were established with unilateral ureteral ligation in rats. Ac-SDKP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Kanasaki et al showed that in human mesangial cells, Ac-SDKP inhibited the TGF-β-induced expression of PAI-1, Smad2 phosphorylation, and promoted the translocation of Smad7 from the cytoplasm to nucleus, which inhibited R-Smad proteins [ 61 ]. Wang et al reported that in UUO rats, Ac-SDKP treatment relieved interstitial fibrosis through the downregulation of TGF-β and α-SMA [ 62 ]. Chan et al reported that in UUO BALB/c mice, the level of AC-SDKP in urine was elevated by captopril treatment and reduced with co-treatment of captopril and S17092.…”
Section: Kidneymentioning
confidence: 99%
“…Kanasaki et al showed that in human mesangial cells, Ac-SDKP inhibited the TGF-β-induced expression of PAI-1, Smad2 phosphorylation, and promoted the translocation of Smad7 from the cytoplasm to nucleus, which inhibited R-Smad proteins [ 61 ]. Wang et al reported that in UUO rats, Ac-SDKP treatment relieved interstitial fibrosis through the downregulation of TGF-β and α-SMA [ 62 ]. Chan et al reported that in UUO BALB/c mice, the level of AC-SDKP in urine was elevated by captopril treatment and reduced with co-treatment of captopril and S17092.…”
Section: Kidneymentioning
confidence: 99%
“…In particular, ( N ‐acetyl‐SDKP) reduces the expression of inflammatory molecules monocyte chemoattractant protein‐1 (MCP‐1), which is one of the most important indicators of the inflammatory process within the renal tubular tissue. This reducing action is correlated with the activation of nuclear factor‐kappa‐B (NF‐κB) (Nussberger et al, 1998b; Wang et al, 2010; Yacoub & Campbell, 2015). Consequently, the antihypertensive behavior of ACE‐1 inhibitors is controlled by selective C ‐ACE domain inhibition; in expense of reduction in antifibrotic activity due to clearance of the active antifibrotic agent ( N ‐acetyl‐SDKP) through unblocked ACE N ‐domain (Cotton et al, 2002; Fuchs et al, 2008; Sharma et al, 2008; Zuo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%